PENINGKATAN HASIL BELAJAR SEJARAH DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA AUDIO VISUAL SISWA KELAS XI IPA2 MAN I MERANGIN - GUSRI YENI (LP2MTBM MAKARIOZ, 2023)
This research is a Classroom Action Research (PTK) aims to determine the learning outcomes of the history of the Indonesian nation's resistance to European colonization in the early XX century by using the Cooperative Integrated Reading and composition (CIRC) learning model assisted by Audio visual in class XI IPA 2 MAN 1 Merangin. The implementation of this PTK was carried out in two cycles. Each cycle includes planning, implementation, observation, and reflection activities. Student learning outcomes were conducted through individual learning outcomes tests. The subjects of this study were students of class XI IPA 2 MAN I Meranginyang totaling 32 people. Based on the initial test (Pre-Action) the percentage of classical completeness was obtained 50%. After using the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by audio visual, the student learning outcomes test in cycle I showed a percentage of classical completeness of 56%. In cycle II, the learning test results were obtained with a percentage of classical completeness of 85%. So it is concluded that there is an increase in the learning outcomes of Indonesian history on the material of Indonesian resistance to European colonization in the early XX century through the Cooperative Integrated Reading and composition (CIRC) learning model assisted by audio visuals in class XI IPA2 MAN I Merangin students.